A method for the production of large volumes of WAF and CEWAF for dosing mesocosms to understand marine oil snow formation. Issue 10 (October 2017) - Wade, Terry L.; Morales-McDevitt, Maya; Bera, Gopal; Shi, Dawai; Sweet, Stephen; Wang, Binbin; Gold-Bouchot, Gerado; Quigg, Antonietta; Knap, Anthony H.
Abstract: Marine oil snow (MOS) formation is a mechanism to transport oil from the ocean surface to sediments. We describe here the use of 110L mesocosms designed to mimic oceanic parameters during an oil spill including the use of chemical dispersants in order to understand the processes controlling MOS formation. These experiments were not designed to be toxicity tests but rather to illustrate mechanisms. This paper focuses on the development of protocols needed to conduct experiments under environmentally relevant conditions to examine marine snow and MOS. The experiments required the production of over 500 liters of water accommodated fraction (WAF), chemically enhanced water accommodated fraction of oil (CEWAF) as well as diluted CEWAF (DCEWAF). A redesigned baffled (170 L) recirculating tank (BRT) system was used. Two mesocosm experiments (M1 and M2) were run for several days each. In both M1 and M2, marine snow and MOS was formed in controls and all treatments respectively. Estimated oil equivalent (EOE) concentrations of CEWAF were in the high range of concentrations reported during spills and field tests, while WAF and DCEWAF concentrations were within the range of concentrations reported during oil spills. EOE decreased rapidly within days in agreement with historic data and experiments.